EFEKTIVITAS PROGRAM KELUARGA HARAPAN DALAM UPAYA PENGENTASAN KEMISIKINAN DI KECAMATAN LEMBANG KABUPATEN BANDUNG BARAT - Fitri Irvanasari (Jurnal Caraka Prabu, 2018)
The research title is "The Effectiveness of the Hope Family Program in Poverty Control Efforts in Lembang District, West Bandung Regency". The problem in this research is the ineffectiveness of the Family Hope Program (PKH) in Lembang District. In this study, using a descriptive method with a qualitative approach. Teaching techniques through literature study, interviews with informants and use of documents. The key informants in this study were the Lembang PKH Assistance Coordinator, as well as supporting informants consisting of UPPKH staff in West Bandung Regency, the Secretary of Lembang District and several PKH participants in Lembang District. Based on the results of the research that the implementation of PKH has been able to reduce the burden on poor community PKH participants, and is able to increase PKH participant participation in accessing health and education, however, there are still some obstacles that show that PKH implementation is less than optimal, this is evidenced by PKH being right on target causing problems , PKH funds that are not in accordance with the circumstances of PKH participants and PKH facilitators, the minimum number of mentors, and disbursement of PKH funds that are not on time. Efforts to overcome these obstacles include updating data, increasing PKH funds, increasing counterpart quota, and extending the time for distribution of funds.